2022
DOI: 10.1002/ps.7223
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of insecticide resistance mutations in source and immigrant populations of the diamondback moth Plutella xylostella (L.)

Abstract: BACKGROUND The diamondback moth (DBM) Plutella xylostella has developed resistance to almost all insecticides used to control it. Populations of DBM in temperate regions mainly migrate from annual breeding areas. However, the distribution pattern of insecticide resistance of DBM within the context of long‐distance migration remains unclear. RESULTS In this study, we examined the frequency of 14 resistance mutations for 52 populations of DBM collected in 2010, 2011, 2017 and 2018 across China using a high‐throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…In our study, KASP genotyping can be performed in 384‐well plates, including 4–8 populations (46/94 individuals per population), giving it much higher throughput than the other methods. Our study showed that KASP is a potential method for high throughput detection of resistant mutations, following our use of this approach in a different context 39,40 …”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In our study, KASP genotyping can be performed in 384‐well plates, including 4–8 populations (46/94 individuals per population), giving it much higher throughput than the other methods. Our study showed that KASP is a potential method for high throughput detection of resistant mutations, following our use of this approach in a different context 39,40 …”
Section: Discussionmentioning
confidence: 86%
“…Our study showed that KASP is a potential method for high throughput detection of resistant mutations, following our use of this approach in a different context. 39,40 However, the two forward primers for the KASP assay need to stop at the mutation site, reducing the flexibility of the primer design. Thus, the KASP assay might be limited for some resistant mutations.…”
Section: Methodological Advantages and Limitations Of Kaspmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that in 2017 and 2018, S. furcifera from the test field populations in Sichuan were at a susceptible or low level of resistance toward pymetrozine; ,, however, our results found that the resistance of some field populations reached a high level of resistance, and the levels of resistance increased rapidly. This is due to the migratory nature of the pest, where its resistance is determined not only by the local practices of insecticide usage and rice varieties in the new area but also by the historical patterns of insecticide usage and resistance in the source population. Consequently, field populations within the same rice area exhibit significant variations in their resistance to insecticides from year to year. In particular, there has been a notable issue with pymetrozine resistance, not only in Sichuan but also in other regions of China.…”
Section: Discussionmentioning
confidence: 99%